Comparison of the efficiency of compensatory growth of Borana and Arsi cattle in Ethiopia - Tolla, N.; Mirkena, T.; Yiemegnuhal, A. (2002)
The efficiency of compensatory growth of 50 Bos indicus (25 Arsi & 25 Borana) bulls with age 28-36 months following different levels of feed restriction for 90 days was studied. The bulls were blocked by weight and randomly assigned to five dietary treatments: ad libitum feeding for the entire period (A), maintenance requirement for 90 days followed by ad libitum feeding for 104 days B), 15% weight loss in 90 days followed by ad libitum feeding for 104 days (C), 20% weight loss in 90 days followed by ad libitum feeding for 104 days (D) and 25% weight loss in 90 days followed by ad libitum feeding for 104 days (E). The feed restriction imposed for treatments C, D and E during the initial period resulted in weight losses of 16%, 20% & 23% respectively. Both daily dry matter intake (DMI) and metabolizable energy intake (MEI) during the restriction period declined with increasing levels of feed restriction. Consequently average daily weight gain (ADG) and metabolizable energy intake (MJ/day). During compensatory feeding period were significantly different among treatments (P<0.05) and breeds (P<0.001). ADG during the compensatory feeding period was also significantly different among treatment (P<0.001) and breeds (P<0.01). Feed restricted groups (C, D and E) exhibited rapid daily weight gains than those managed under ad libitum (control) and maintenance feeding levels. Recovery index was not significantly (P>0.05) different among treatments, but significantly (P<0.05) different between breeds. Arsi bulls had higher (59%) recovery index than Borana bulls (30%). Even though the overall TDMI and MEI during compensatory feeding were increased by four folds than during the restriction period, animals under treatments B, C, D and E could not attain complete compensation within 104 days of compensatory feeding. But Arrsi bulls managed under maintenance feeding level recovered 96% of their weight loss after 104 days of compensatory feeding as compared to Borana bulls (25%) managed similarly. The overall carcass weight indicated declining trend with increasing levels of feed restriction. The results of this study indicated that responses to compensatory feeding are influenced by either severity of under nutrition, breed type of cattle or duration of compensatory fending. The optimum time and cost-benefit relationships at which complete recovery can be attained after a period of feed restriction require further investigation.